Integrated 'one-stop' support for student success: recommendations from a regional university case study. Issue 3 (15th April 2020) - Power, Emma; Partridge, Helen; O'Sullivan, Carmel; Kek, Megan Yih Chyn A.
ABSTRACT: Cohesive integration practices within 'one-stop' student support services are critical for student success, however empirical studies in this area are limited in number and scope. This case study addresses this gap by exploring the lived experience of staff and managers who support students at a regional Australian university's integrated student service. This integrated service provides students with support through the following services: the library, ICT help, student support and retention, learning support and student services. Semi-structured interviews with integrated service managers and staff, alongside observations of front-facing staff and students, provided the data set for this research. Thematic analysis was used to code 18 interview transcripts and seven observation journal entries to analyse and develop themes of experience. The five identified themes form a hierarchal relationship across individual and interpersonal levels of participant experience. On the individual level, are the themes of understanding, skills and student-centred philosophy. Building upon these individual-level themes are the two interpersonal level themes of communication and collaboration. Recommendations derived from these findings encompass practical strategies for universities looking to enhance their integrated service point operations. These strategies include comprehensive professional development, enhancing communication and supporting collaborations. Overall, this case study highlights the critical interpersonal and individual factors that affect this integrated service's ability to support student success.